2018
DOI: 10.1051/e3sconf/20186403003
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Evaluation of Energy Storage Systems Built from EV Batteries – Prospective Revenues in Different Stationary Applications

Abstract: Battery energy storage systems (BESSs) are already being deployed for several stationary applications in a technically and economically feasible way. This paper focuses on the revenues of industrial BESSs built from electric vehicle lithiumion batteries with varying states of health. For this analysis, a stationary BESS simulation model is used, that is parameterised with parameters of a 22-kWh automotive battery. The comprehensive model consists of several detailed sub-models, considering battery characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The majority of the literature on battery ageing in second-life applications focuses on firstuse in EVs [7, 32, 37, 49, 50, 56, 57, 61-63, 65, 66, 68-70, 74, 78], which is why it is still a relatively new issue. Only a small number of studies [36,61,80,81,89,95,96] have specifically looked at battery ageing during primary and secondary usage, also, almost all of these studies employ the same ageing models created for first-use. The ability to accurately conduct battery health estimation during second-life applications, which is essential for extending the battery's usable life, is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the literature on battery ageing in second-life applications focuses on firstuse in EVs [7, 32, 37, 49, 50, 56, 57, 61-63, 65, 66, 68-70, 74, 78], which is why it is still a relatively new issue. Only a small number of studies [36,61,80,81,89,95,96] have specifically looked at battery ageing during primary and secondary usage, also, almost all of these studies employ the same ageing models created for first-use. The ability to accurately conduct battery health estimation during second-life applications, which is essential for extending the battery's usable life, is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that researchers and stakeholders conduct cost analysis of battery screening, refurbishment, and repurposing for specific applications. There have been various techno-economic tools reported in the literature, such as Return on Investment [62,66,96], Return Rate on annual basis [89], Levelized Cost of Energy [36,91] and Levelized annual Cost of Energy using Net Present Value [93,95], Benefit-cost Ratio [61], and cost-optimization algorithms [77,80,94] for economic analysis, but these are based on several assumptions and are applicable only for specific battery compositions and controlled gridconnected applications [61,66,80,90]. These economic studies have mostly confirmed the cost benefits of second-life batteries over new batteries in terms of decrease in LCOE [91,93], increased annual revenue [36,61,70,92] and operating as well as payback years [89,90,92] but it should be noted that these results cannot be generalized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations